Penggunaan SIG Untuk Menentukan Biaya dan Melihat Integrasi Transportasi Umum KRL dan Transjakarta di Jakarta - Sadam, Sadam (Jurnal Sains Geografi, 2024)
Jakarta as the center of economic activity and a city with a large population. This city needs public transportation that can cover the entire area. In addition, public transportation also needs to be integrated to facilitate mobility from one mode of transportation to another. However, the ignorance of residents about the cost and integration of public transportation in Jakarta is a factor that makes them choose to use personal vehicles. To overcome this problem, researchers conducted research using Geographic Information Systems (GIS) using descriptive methods with buffering analysis techniques to determine the integrity between KRL stations and Transjakarta bus stops and also using measure tools to determine the distance between stations. This research is purposed to find out the amount of KRL tariff that has been set by the government and to see whether public transportation between KRL and Transjakarta has been integrated or not. The results showed that only 22 out of 44 KRL stations were integrated with Transjakarta BRT stops. In addition, by using GIS, researchers can find out the actual distance between two KRL stations. This low percentage of public transportation integration shows that the government needs to play a role in building integrated public transportation. Public transportation integration will be able to increase public transportation users in Jakarta.